Preparing Urban Water Use Efficiency Plans A Best Practice Guide - Maddaus, Michelle (IWA Publishing, 2013)
Many communities are facing water scarcity in developing and developed countries alike. There are numerous publications and on-going research studies documenting the changes in our climate and potential for worsening shortages in our future. Meeting future potable water demands as communities continue to grow will rely heavily on using our existing water resources more efficiently.Preparing Urban Water Use Efficiency Plans provides detailed approaches to developing and implementing a water conservation plan. This book covers the broad spectrum of conservation planning for urban communities including achieving more efficiency from: Residential domestic uses, Commercial and governmental facilities use, Industrial uses, Pricing Water Loss Control Programs.The steps in the Guide clearly outline and provide sample calculations to aid determining which water use efficiency activities are financially justifiable to undertake. The end result is a plan that policy decision makers can adopt and fund, and that water service provider staff can implement to help increase their community's water reliability. It includes numerous case studies and a Microsoft Excel based software tool to allow planners to evaluate the business case for implementing various water conservation activities. This book is an essential resource for professionals in water and wastewater resources, particularly for planners and engineers. It is also a useful guide for Post Graduate and Undergraduate students.